The Remaking and Unmaking of Multi-Ethnic Spaces : Diyarbakir and Southeast Anatolia in the 21st Century - Gourlay, William (Poligrafi, 2021)
Focusing on 21st century developments in southeast Anatolia, this article examines the circumstances of minority communities within the contexts of the shifting dynamics of Turkey’s national project. Until the early 20th century southeast Anatolia was an ethnic patchwork. The early republican era saw efforts to “Turkify” through the promulgation of a national identity project asserting ethnic unity. From the 1980s, conflict with the PKK gave urgency to the notion that uniformity was paramount for national cohesion. In this milieu, ethnic diversity was suspect. Circumstances changed with the AKP government’s 2002 ascendance and the earlier emergence of Kurdish municipal politicians. This article documents how thereafter the re-imagining of the national project away from an exclusive ethnic categorisation allowed acknowledgement and accommodation of ethnic and religious diversity across southeast Anatolia. The chapter analyses these events in light of a backlash by nationalist politicians, the 2015 re-ignition of the PKK conflict and the subsequent resurgence of nationalist rhetoric in the political arena. It appears a narrow, exclusive national identity is re-asserting itself. The article thus examines the extent to which the experience of south-eastern Anatolia represents the re-imagining of Turkey’s national project and the embrace of a previously denied multi-ethnic socio-political fabric.